1995
DOI: 10.1063/1.469762
|View full text |Cite
|
Sign up to set email alerts
|

The computation of electron transfer rates: The nonadiabatic instanton solution

Abstract: A computational theory for determining electron transfer rate constants is formulated based on an instanton expression for the quantum rate and the self-consistent solution of the imaginary time nonadiabatic steepest descent approximation. The theory obtains the correct asymptotic behavior for the electron transfer rate constant in the nonadiabatic and adiabatic cases, and it smoothly bridges between those two limits for intermediate couplings. Furthermore, no assumptions regarding the form of the diabatic pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 33 publications
3
56
0
Order By: Relevance
“…This effort clarifies and extends the preliminary work of Ref. 7, which sought to calculate nonadiabatic tunneling rates following in the vein of Pechukas' hybrid semiclassical/quantum theory. 8 To begin, one assumes the validity of the unified activated rate formula 9…”
Section: Introductionsupporting
confidence: 61%
See 2 more Smart Citations
“…This effort clarifies and extends the preliminary work of Ref. 7, which sought to calculate nonadiabatic tunneling rates following in the vein of Pechukas' hybrid semiclassical/quantum theory. 8 To begin, one assumes the validity of the unified activated rate formula 9…”
Section: Introductionsupporting
confidence: 61%
“…This paper should also be seen as superseding the preliminary work of Ref. 7. As a next step, a comparison of the results from the present theory with exact quantum dynamical results for model problems is desirable to test the accuracy in the regime of intermediate coupling.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…For these, a more general approach is needed which correctly gives the limiting cases in both the strong-and weak-coupling regimes. Some suggestions have been given as to how instanton theory could be extended to describe these reactions, 104 but as they are based on the "Im F" premise, they do not appear to give a reasonable classical high-temperature limit. Further work is needed to benchmark these approaches and to apply them to realistic problems.…”
Section: Further Developmentsmentioning
confidence: 99%
“…͑However, encouraging progress in the latter arena has been been reported by Wolynes, 17 and we will make contact with and extend this intriguing point of view from a different perspective.͒ In a recent paper, it was shown that significant progress toward the calculation of ET rate constants for general systems can be achieved by exploring the structure of instanton theory in systems influenced by nonadiabatic transitions. 18 To briefly review this perspective, the approach 18 is based on the instanton expression for quantum rate constants [19][20][21][22][23] combined with a nonadiabatic dynamics formalism 24,25 adapted to treat the imaginary time instanton trajectory undergoing nonadiabatic transitions. As will be discussed later, this mathematical formalism is also contained within the um-brella of a unified theoretical framework for quantum activated rate constants, as was developed in Ref.…”
Section: Introductionmentioning
confidence: 99%